GE_GERICHTE P/15301/2020 vom 15. April 2024 - GE Cour de justice (2024)
ESCROQUERIE;PERCEPTION ABUSIVE DE PRESTATIONS DE L'AIDE SOCIALE;DIFFAMATION;BONNE FOI SUBJECTIVE;PREUVE LIBÉRATOIRE | CP.146; CP.173; CP.173.al2; CP.53